(untitled) (Scientific journal of the Fergana State University, 2025)
The article "Aggression as a Form of Speech Influence in the Literature of the Uzbek and English Languages" explores the role of aggression as a tool for influencing speech within the literary contexts of Uzbek and English languages. This study delves into how aggression is utilized as a rhetorical device, examining its impact on communication and discourse in literary works. Through a comparative analysis of aggression in Uzbek and English literary traditions, this article sheds light on the cultural and linguistic nuances that influence the portrayal and interpretation of aggressive speech in literature. The findings of this study are likely to offer valuable insights into the intersection of language, emotion, and narrative technique, enriching our understanding of the complexities of speech influence in literary works across different linguistic and cultural landscapes.